2020
DOI: 10.1007/s11606-020-05868-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Trustworthiness to Conduct Medical Research: Findings from Focus Groups Conducted with Racially and Ethnically Diverse Adults

Abstract: BACKGROUND: Potential research participants, particularly those from racial and ethnic groups underrepresented in medical research, often decide to participate based on how they judge people, places, and study protocols as trustworthy. And yet, few studies have explored notions of trustworthiness or determinants of trustworthiness from the perspective of potential medical research participants. OBJECTIVE: This paper describes how racially and ethnically diverse potential medical research participants conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“… 30 Prior work has found that individuals from underrepresented racial and ethnic groups’ willingness to participate in research stems from perceived trustworthiness of the researchers, the institutions conducting the research, and the information provided about the applicable research studies. 31 There may be more mistrust surrounding genetic and biological studies—for example, genetic counseling participation is low among Black women for BRCA1/2 testing. 32 This finding was exacerbated among women with higher rates of medical mistrust, 32 fear of discrimination by insurance companies if considered high-risk, 33 and fear of carrying the mutation.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Prior work has found that individuals from underrepresented racial and ethnic groups’ willingness to participate in research stems from perceived trustworthiness of the researchers, the institutions conducting the research, and the information provided about the applicable research studies. 31 There may be more mistrust surrounding genetic and biological studies—for example, genetic counseling participation is low among Black women for BRCA1/2 testing. 32 This finding was exacerbated among women with higher rates of medical mistrust, 32 fear of discrimination by insurance companies if considered high-risk, 33 and fear of carrying the mutation.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Similarly, a recent study discussed the concerns of AA participants and their skepticism of certain researchers given historical unethical research practices. 32 The authors further highlighted the importance of a shared background and understanding between researchers and participants as was shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these strategies explicitly consider how the historical legacy of racism or discrimination ( Ford et al, 2019b )—in its unique population-specific forms—is important to address to overcome a legacy of distrust and mistrust that may adversely affect participation in research ( Griffith, Bergner, et al, 2020 ; Jaiswal & Halkitis, 2019 ). These three conceptual pieces (including the scoping review) also explicitly use a range of strategies that facilitate trustworthiness or efforts to move the responsibility of issues related to trust from research participants or health-care patients to the researchers and providers using processes that engender trust in research and clinical practice ( Crawley, 2001 ; Griffith, Jaeger, et al, 2020 ; Jaiswal, 2019 ). Finally, Sinclair and colleagues, Williams and colleagues, and Dhillon and colleagues explicitly incorporate notions of positive masculinities or positive attributes (e.g., dignity) that provided an important foundation of assets and strengths rather than treating gendered notions in men’s health as only having toxic or negative forms.…”
Section: Discussionmentioning
confidence: 99%